Diseases: Detached retina-gallstones - Bunch, Bryan H.; Grolier Educational (Firm) (Danbury, CT : Grolier Educational, 1997)
Alphabetically arranged articles present medical information on more than 400 diseases, discussing sources, symptoms, stages of the disease, its likelihood of striking, treatments, prevention, and long-term effects.
"A Hudson Group book."
Includes index.
Keywords: Diseases